2016
DOI: 10.1186/s12860-016-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

The absence of dysferlin induces the expression of functional connexin-based hemichannels in human myotubes

Abstract: BackgroundMutations in the gene encoding for dysferlin cause recessive autosomal muscular dystrophies called dysferlinopathies. These mutations induce several alterations in skeletal muscles, including, inflammation, increased membrane permeability and cell death. Despite the fact that the etiology of dysferlinopathies is known, the mechanism that explains the aforementioned alterations is still elusive. Therefore, we have now evaluated the potential involvement of connexin based hemichannels in the pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
(52 reference statements)
2
24
0
Order By: Relevance
“…As compared with C25 myoblasts, the expression of dysferlin was reduced by 68%, 87%, 88%, and 83% in DYSF2, DYSF3, AB320, and ER myoblasts, respectively. These results agree with the expected dysferlin expression in these myoblasts [31,32,36,37] and validate these cell lines as in vitro models of dysferlinopathy. We first analyzed the relative expression of dysferlin in the cell lines DYSF2, DYSF3, AB320, and ER and compared it with the expression of the protein in C25 control myoblasts.…”
Section: Dysferlin Expression In the Dysferlinopathy Cell Linessupporting
confidence: 88%
See 2 more Smart Citations
“…As compared with C25 myoblasts, the expression of dysferlin was reduced by 68%, 87%, 88%, and 83% in DYSF2, DYSF3, AB320, and ER myoblasts, respectively. These results agree with the expected dysferlin expression in these myoblasts [31,32,36,37] and validate these cell lines as in vitro models of dysferlinopathy. We first analyzed the relative expression of dysferlin in the cell lines DYSF2, DYSF3, AB320, and ER and compared it with the expression of the protein in C25 control myoblasts.…”
Section: Dysferlin Expression In the Dysferlinopathy Cell Linessupporting
confidence: 88%
“…Four different cell lines of immortalized myoblasts were derived from skeletal muscle biopsies from dysferlinopathy patients. These cell lines named DYSF2 (also called 107), DYSF3 (also called 379), AB320, and ER myoblasts were previously characterized [31,32]. Table 1 describes the origin of each cell line, including the mutations carried by donors.…”
Section: Dysferlin Expression In the Dysferlinopathy Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this statement, depletion or reduction of CD4+ or CD8+ T cells [94] or neutrophils [95] in mdx mice reduces the severity of the dystropathology. In addition, mdx myofibers were recently shown to express de novo three connexins (39, 43 and 45) [96]. Accordingly, myofibers of DMD or BMD patients were found to express connexins 45.…”
Section: Connexins and Pannexins In Skeletal Musclementioning
confidence: 99%
“…In agreement with a local inflammatory response and the role of connexin hemichannels, it was recently demonstrated that connexin hemichannels also participate in LGMDs. In immortalized myotubes derived from patients harboring dysferlin mutations, it was found that connexin hemichannels are still expressed in mature myotubes and are responsible of an increase (~10%) of basal cytoplasmic Ca 2+ levels, suggesting that these hemichannels could mediate the posterior muscle atrophy and adult myofibers death [96]. …”
Section: Connexins and Pannexins In Skeletal Musclementioning
confidence: 99%